Assessment of depression and sexual quality of life in postmenopausal women. Issue 4 (12th January 2022) - Duzgun, Ayten Arioz; Kok, Gulsah; Sahin, Sevil; Guvenc, Gulten
Abstract: Purpose: To determine the prevalence of depression, review some variables that are believed to be associated and assess the relationships between depression and sexual quality of life in postmenopausal women. Design and Methods: This is a cross‐sectional study conducted on postmenopausal women in Ankara, Turkey from February to June 2020. The study group consisted of 242 postmenopausal women. The Beck Depression Inventory and Sexual Quality of Life Questionnaire were used to assess the level of depression and sex life, respectively. Online questionnaire forms (Google Form) prepared by using the literature in line with the study objective were completed by the women online. Independent t ‐test, analysis of variance, Tukey's test, and Pearson's correlation analysis were used for statistical analyses. Statistical significance was accepted as p ≤ 0.05. Findings: The of women was found to be 52.64 (±6.245) years and the average menopause age was found to be 47.81 (±4.039) years in this study. The mean score obtained by the women from the Beck Depression Inventory was 13.04 (±7.82). It was determined that the women showed "mild depressive symptoms" mostly. As for the women's sexual quality of life, the mean score obtained from the Sexual Quality of Life Questionnaire was 61.32 (±14.70). A statistically significant and moderate negative correlation was detected between the mean scores obtained by the women from the Beck Depression Inventory and the Sexual Quality of Life Questionnaire ( r = −0.305; p < 0.01). Practice Implications: It was determined in the study that sexual quality of life is affected by menopause negatively and the women had mild depressive symptoms. Depression among postmenopausal women is an important women's health problem that should be addressed. A negative correlation was found between depression and sexual quality of life. Early diagnosis and treatment of menopause as well as activities for raising awareness among postmenopausal women will be effective in improving quality of life.